Vozrastnaja dinamika stanovlenija vzryvnoj sily myšc ruk u lyžnikov-gonšcikov v sportivnom ontogeneze - Golovachev, A. I.; Abramova, T. F.; Dyshko, B. A.; Shirokova, S. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
n the article, the data on age dynamics of formation of indicators of the explosive strength of the hands of the athletes on the stages of development of age and sport ontogenesis. In the process of the study showed that the development of explosivestrength of the arms, evaluated at the value made of fur technical work in one movement (imitation of the simultaneous courses of the skier) performed with maximum power, most actively occurs in the age period from 13-14 to 19-22 years, from the beginning of puberty and to entry into the period of adulthood. The criterion for the final formation of the studied indicators is the achievement of the definitive values due to the termination of statistically significant gains between the previous and subsequent stages of growth development. The age period from 23 to 28 years is characterized by the stabilization of the studied parameters with the variability in the range from -1.8 to 3.3%, determined within the individual variability in the groups. The increased dynamics of age formation of indicators of explosive strength of hand muscles indicates the existing time lag of active growth processes (achievement of the maximum growth rate) in relation to the indicators of explosive strength of leg muscles in the range of one year.